Place and space in the medieval world - Boulton, Meg; Hawkes, Jane; Stoner, Heidi (Routledge, 2018)
This book addresses the critical terminologies of place and space (and their role within medieval studies) in a considered and critical manner, presenting a scholarly introduction written by the editors alongside thematic case-studies that address a wide range of visual and textual material. The essays consider the extant visual and textual sources from the medieval period alongside contemporary scholarly discussions to examine place and space in their wider critical context, and are written by specialists in a range of disciplines including art history, archaeology, history and literature
Keywords: Geschichte 500-1500; Kunst; Sozialraum; Architektur; Geografischer Raum; Kartografie; Kultur; Raumwahrnehmung; Konferenzschrift -- 29.05.2015-31.05.2015 -- University of York